Residual strength assessment of corroded ships involved in ship-to-ship collisions - Baxevanis, Dimitrios (My University, 2019)
Ships and marine structures are forced to operate in a very complex environment with corrosion to be regarded as one of its main features. Another crucial aspect of shipping operation is the ship collisions. The possibility of an accidental collision can’t be ignored due to the increase of traffic density. The objective of the present study is to estimate the ultimate strength of damaged ships considering the effects of material degradation due to corrosion. A review of the corrosion models, which can be used for the prediction of the thickness reduction of the hull, is included. The structural damage of non-corroded and corroded ships involved in ship collisions are calculated by nonlinear FEA. The Smith-Fujikubo method is applied for the residual strength assessment of the damaged ship under biaxial loading conditions. The largest reduction of the ultimate strength is observed when the most severe structural damage appears in a corroded hull showing a correlation between residual strength and corrosion presence. The most significant ultimate strength decrease is found in loading directions, which do not correspond to hogging and sagging conditions concluding the importace of the biaxial loading in the residual strength assessment.
Keywords: Biaxial loading; corrosion; corrosion models; material degradation; residual strength; ship collisions; ultimate strength